2020
DOI: 10.1002/iub.2268
|View full text |Cite
|
Sign up to set email alerts
|

HbA1c in patients with intracranial meningiomas WHO grades I and II: A preliminary study

Abstract: Meningiomas are among the most common primary brain tumors. There is a growing need for novel ways of differentiating between benign (World Health Organization [WHO] grade I) and atypical (WHO grade II) meningiomas as well as for novel markers of the tumor's future behavior. A difference between glucose metabolism in atypical and benign meningiomas is well known. However, a significant correlation between the systemic metabolic status of the patient and the meningioma WHO grade has not yet been established. Ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
0
1
1
Order By: Relevance
“…2 A). Contrary to our preliminary research [ 43 ], in the current study there was no significant correlation between the patients’ HbA1c and Ki67 values ( P = 0.8815, ρ(rho)=-0.018) (Fig. 2 B).…”
Section: Resultscontrasting
confidence: 99%
“…2 A). Contrary to our preliminary research [ 43 ], in the current study there was no significant correlation between the patients’ HbA1c and Ki67 values ( P = 0.8815, ρ(rho)=-0.018) (Fig. 2 B).…”
Section: Resultscontrasting
confidence: 99%
“…These alterations to various aspects of metabolic syndrome have on the other hand been consistently connected to a worse prognosis in patients with cancer ( 57 ), as well as with malignant brain tumors ( 58 , 59 ). Our own preliminary research on patients with meningiomas ( 60 ) and patients with glioblastomas ( 61 ) showed that at least some patients with primary intracranial malignancies could actually have significantly disrupted chronic blood glucose levels. Even on the cellular level, it has been shown that genes coding for various glucose transporters (GLUT1 for example) are differently expressed in the sleeping brain than in the awake one ( 46 ).…”
Section: Systemic Effects Of Disrupted Sleepmentioning
confidence: 99%